Case Report: False vertebral artery stenosis: an rare phenomenon - Nao, Yan; Niao, Yang; Dong, Sun; Bin, Mei (Frontiers in Surgery, 2025)
IntroductionTrans-radial access (TRA) has gained widespread adoption in neurointerventional procedures, particularly for cerebral angiography. The success of trans-radial cerebral angiography crucially relies on the proper formation of the simmons-2 catheter loop to navigate the aortic arch and selectively catheterize the cerebral vessels. However, the potential of simmons-2 catheter loop configuration to induce angle change of the vasculature was not previously recognized in our institutional practice.MethodsWe present a rare cerebrovascular imaging phenomenon identified during diagnostic and therapeutic neurointerventional procedures in a 60-year-old male patient. Selective cerebral angiography performed via right radial access demonstrated severe ostial stenosis of the right vertebral artery. Thus, endovascular stent placement was scheduled to address the right vertebral artery stenosis via trans-radial approach. Surprisingly, intraoperative vertebral artery angiography via 6F guiding catheter demonstrated complete resolution of the preoperative stenosis. We conducted a comparative analysis of subclavian artery and brachiocephalic trunk morphology using pre- and post-loop formation angiographic imaging.ResultsAngiographic analysis revealed that the simmons-2 catheter loop configuration resulted in a significant alteration of the angle between the horizontal subclavian artery and the descending brachiocephalic trunk, producing vertebral artery traction and apparent stenosis.DiscussionThe discrepancy arose from a previously unrecognized phenomenon: simmons-2 catheter loop configuration altered the angulation between the vessels, resulting in artefactual vertebral artery ostium stenosis during initial angiography. This case reveals previously unrecognized anatomic-vascular interactions influencing for trans-radial neurointerventional procedures. This report carries significant implications for procedural techniques and image interpretation in neurointerventional practice.